Control of the receptor binding to a ligand-containing monolayer at the air/water interface by the lateral pressure: A film balance and neutron and infrared reflection study - Maierhofer, Andreas; Braun, Martin; Vostrowsky, Otto; Hirsch, Andreas; Langridge, Sean; Bayerl, Thomas (Journal of Physical Chemistry B, 2001)
We have studied the structure of a binary monolayer of dipalmitoylphosphatidylcholine (DPPC) and a biotinylated amphiphilic fullerene (BF) as a function of the lateral pressure. The compression isotherm of the mixture exhibited two separate kinks with a remarkably flat plateau after the second kink. Neutron and infrared reflection measurements suggest that upon compression of the mixed monolayer a (reversible) vertical shift of the BF occurs, leading to a (partial) demixing of the two components in the third dimension at high lateral pressure. As a consequence, the biotin group attached to the BF becomes inaccessible to streptavidin binding from the subphase at high lateral pressure, while the binding is clearly observed at low pressure. © 2001 American Chemical Society.